Perceptions and experiences of antiretroviral treatment (ART) of patients in Themba Lethu Clinic in Johannesburg : an exploratory study. - Mongwenyana, Constance (My University, 2012)
Background – The researcher conducted an explorative, qualitative study to identify the perceptions and experiences about ART of patients currently on treatment at Themba Lethu clinic (TLC) in Johannesburg in order to establish strategies to decrease the high level of non-adherence to antiretroviral therapy (ART). This study included 30 HIV positive patients on ART who came to Themba Lethu clinic for their regular clinic visit. The researcher used the purposive sampling procedure to target particular individuals and categories of individuals for investigation. Interviews and questionnaires were used as a method of collecting primary information. The researcher posed a series of questions to willing participants about their characteristics, opinions, attitudes, or previous experiences by and tabulates their answers. Results – The research finds that the participants ‘ages ranged from 26 – 62 years (M = 39.4). The participants stay in the suburbs around Johannesburg in Gauteng and 77% of them have been living there for more than 5 years. Only 40% of these patients were originally born in Gauteng while others come from different provinces in South Africa including some of the sub-Saharan countries (13%). The participants were less likely to have completed secondary education but were more likely to have completed Matric. 30% of participants are afraid of stigma, 40% are concerned about side-effects, 33.33% believes that ART cures AIDS, 70 % are non-adherent and 20% visited traditional healers while on ART. Conclusion – There must be on-going education, counseling and support to increase adherence and decrease the clinic loss to follow-ups. Intervention to improve care and treatment should utilize the role of traditional healers to reduce the disease progression and to improve adherence to ART. Traditional healers could also work more closely with modern health professionals to provide AIDS information and evaluation of HIV/AIDS symptoms.
Keywords: Antiretroviral treatment; Themba Lethu Clinic; Patients